Declining malaria transmission differentially impacts the maintenance of humoral immunity to plasmodium falciparum in children - Mugyenyi, Cleopatra K.; Elliott, Salenna; Osier, Faith (The journal of infectious diseases, 2017)
Declining malaria transmission results in reductions in total antibodies to merozoite antigens in children. However, some important functional antibodies and an